2014
DOI: 10.1111/jace.13144
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance Induced by Cr Doping at Ca‐Sites in Ca3Co4O9 System

Abstract: Thermoelectric performance of Ca3Co4O9 system has been enhanced through the misplaced substitution with Cr doping at Ca‐sites. The study of Cr doping at Co‐sites has also been performed for comparing. Base on the analysis of the structural data, we conclude that the doped Cr ions should be in the form of Cr+6, and enter into Ca‐sites of Ca2CoO3 layers in Ca3−xCrxCo4O9 lattice and Co‐sites of CoO2 layers in Ca3Co3.90Cr0.10O9 lattice, respectively. As Cr ions are doped into Ca‐sites in Ca3−xCrxCo4O9 lattice, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Actually, such a misplaced substitution idea has been explored. For example, the substitutions of Cr for Li in LiFePO 4 structure, Cr for Ca and Ag for Co in Ca 3 Co 4 O 9 one, respectively. , In the former, the electric conductivity was enhanced by 8 orders of magnitude via Cr doping. Accordingly, such an enhancement would be greatly conductive to the improvement of TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, such a misplaced substitution idea has been explored. For example, the substitutions of Cr for Li in LiFePO 4 structure, Cr for Ca and Ag for Co in Ca 3 Co 4 O 9 one, respectively. , In the former, the electric conductivity was enhanced by 8 orders of magnitude via Cr doping. Accordingly, such an enhancement would be greatly conductive to the improvement of TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6b presents data for the variation of cobalt species in Ca 2.7 Bi 0.3 Co 3.92 O 9+δ ceramics before and after annealing at 1203 K. Cobalt is present in three valences in the Ca 3 Co 4 O 9 lattice: Co 2+ exists in the rock salt layers while Co 3+ and Co 4+ coexist in the CoO 2 layers. 42 The Co 2p 3/2 spectra are deconvoluted into three peaks, where the first peak at 779.26− 779.30 eV corresponds to Co 3+ , the second peak at 780.26− 780.30 eV is assigned to Co 2+ , and the third at 782.06−782.10 eV is ascribed to Co 4+ . These results are consistent with published Co 2p XPS data 43−45 and confirm a mixture of valence for cobalt in the calcium cobaltite lattice.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In fact, the misfit ratio between the [CoO 2 ] layer and the [Ca 2 CoO 3 ] layer is not exactly a rational number but approaches the golden ratio τ ≈ (1: 0.618) [25]. It was reported that mixed cobalt valence states occur in the calcium cobaltite lattice, where Co 2+ exists in the rock salt layers, while Co 3+ and Co 4+ coexist in the [CoO 2 ] layers [27]. By preserving charge neutrality in the different layers, electrons are transferred from the negatively charged [CoO 2 ] layers to the positively charged [Ca 2 CoO 3 ] layers, thereby generating hole carriers in the [CoO 2 ] layers [28].…”
Section: Crystal Structurementioning
confidence: 99%
“…As the substitution of Ca 2+ by higher valence ions (e.g. Cr 6+ , La 3+ , Eu 3+ , Bi 3+ ) [27,39,50,51] generates electrons, the hole concentration is expected to be reduced. However, these substituting ions have larger atomic mass or size than Ca 2+ ions, which gives rise to obvious strain and mass variations.…”
Section: Elemental Dopingmentioning
confidence: 99%
See 1 more Smart Citation